Addiction and stress: An allostatic view - Koob, George F.; Schulkin, Jay (Neuroscience and biobehavioral reviews, 2019)
•Allostatic stress represents a challenge to emotion-related brain circuit regulatory mechanisms.•Stress alters function in all three stages of the addiction cycle.•Stress contributes to dysregulation of incentive salience/habits, negative emotional states, and executive function.•Stress-induced neurocircuitry dysregulation is involved in the transition to pathophysiology. Allostasis, or stability through change, has most often been linked with challenges to homeostasis, in which repeated challenges or stressors produce sufficient allostatic load to generate an allostatic state that can ultimately lead to a disease state. The present review argues that the impact of stress on drug addiction fits with an allostatic model and represents a challenge to brain circuit regulatory mechanisms that underlie the emotional state of the animal. The central thesis is that stress leads to changes in corticotropin-releasing factor in the brain that impact addiction. Stress is further argued to impact all three stages of the addiction cycle—binge/intoxication, withdrawal/negative affect, and preoccupation/anticipation—exposing the animal to an emotional allostatic load and allostatic state that forms the growing motivational pathology of addiction. Viewing addiction as an allostatic mechanism provides key insights into the ways in which dysregulated neurocircuitry that is involved in basic motivational systems can transition to pathophysiology.